AN ANALYSIS ON THE STRATEGY OF TEACHING AND LEARNING PROCESS OF READING SKILL AT MATHAYUM ISLAM BACHOK WITTAYA SCHOOL THAILAND - Sariakin (Getsempena English Education Journal, 2020)
The researcher discusses about the strategy of teaching and learning Process that is done by a teacher. The strategy is the ability of a teacher to design the learning environment and the talents of its students become better, focused, and organized so that time can be used efficiently. This research aims (1) to find out how the teaching and learning process of reading skill is applied by the English teachers of Mathayum Islam Bachok Wittaya School is, and (2) to find out how the impact of the strategy that is applied by English teachers Mathayum Islam Bachok Wittaya for the students’ ability in mastering reading texts is. The design used in this research is descriptive research. Thus, this research belongs to qualitative research because only describes the strategy that is used by the teachers in conducting teaching and learning process of reading skill at the school. The subjects of this research were two teachers who teach English. The instruments that was used to collect data were observation, interview, and documentation. The data gotten was analyzed by narration procedure and discussion. The result of research showed the teachers used to use various strategies that aimed to make the students not bored. Although the teachers used to use various strategies, the teachers usually used jigsaw technique in teaching and learning process. The strategy that was applied the teachers of Mathayum Islam Bachok Wittaya School in teaching and learning process of reading skill was effective. Thus, the strategy that was used by the teachers had a good impact for the students’ ability in mastering reading text. It was proven that the students’ average score in mastering reading skill after teaching in learning process was 80 and it was higher than the standard score. Meanwhile, the standard score of reading skill was 75 at the school.